Recetario didáctico audiovisual como promotor de Educación Alimentaria Nutricional en Nivel Inicial. Evaluación del impacto en jardines de la ciudad de Santa Fe (FABICIB, 2025)
An Audiovisual Didactic Recipe Book (RDA) was validated to be used as an educational tool by Initial Level teachers, considering that they are the ones who play a key role in the first stages of the lives of boys and girls.The RDA was created by the extension team of Extension and Social Interest Projects, Territorial Extension Actions and Extension and Institutional Interest Projects anchored in the Faculty of Biochemistry and Cs. Biological, from the National University of the Litoral. A qualitative, descriptive and exploratory study was carried out, adopting the research-participatory action modality in Gardens that make up the Physical Education Center (CEF) No. 4 Laureano Maradona.The RDA was used by teachers during 2021 through virtuality and socialized through in-person workshops through the thesis student and graduate students in Nutrition. The reaction of the boys and girls was observed, discussion groups were formed with teachers to evaluate their implementation and the strategies they carried out for their socialization.All the information obtained was collected and criteria were unified. The data obtained was positive in terms of design and implementation, resulting in the RDA being an instrument consistent with the Initial Level.